2021
DOI: 10.1177/01455613211051651
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Sialogram Correlates to Parotid Immunoglobulin G4-Related Disease

Abstract: Immunoglobulin G4 (IgG4)-related disease is an immune-mediated disorder that commonly manifests in the salivary glands. As a recently described disorder, the description and classification of IgG4-related disease is an ongoing process. Diagnosis of IgG4-related disease requires integration of clinical history, histopathology, and radiographic findings, including ultrasonography and sialography. In this case report, we correlate parotid ultrasonographic and sialographic findings in a patient with proven IgG4-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Sialography remains an important tool in the diagnosis of salivary gland disease, further refined with introduction of the Iowa sialogram classification system to offer consistency in classifying pathology within parotid and submandibular ducts. 6,18,19 Contemporary high quality digital infusion sialography is primarily designed as a diagnostic tool to direct care but often provides ancillary benefit as a therapeutic measure in the course of duct dilation with irrigation. 5,9 Although adverse effects to iodinated contrast are rare during sialography, the standard precaution involving pretreatment with steroids and diphenhydramine may be either refused or not tolerated by patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sialography remains an important tool in the diagnosis of salivary gland disease, further refined with introduction of the Iowa sialogram classification system to offer consistency in classifying pathology within parotid and submandibular ducts. 6,18,19 Contemporary high quality digital infusion sialography is primarily designed as a diagnostic tool to direct care but often provides ancillary benefit as a therapeutic measure in the course of duct dilation with irrigation. 5,9 Although adverse effects to iodinated contrast are rare during sialography, the standard precaution involving pretreatment with steroids and diphenhydramine may be either refused or not tolerated by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature identified a single case‐study documenting the use of gadolinium as an alternative contrast for sialography in patients with iodine allergies 16 . We compared the use of gadolinium in a series of six sialograms with similar sialograms performed with traditional iodinated contrast agents, using the University of Iowa sialogram classification system as an objective reference, adapted previously from the Iowa parotid sialogram classification system 17–19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation